PENGARUH MUTASI KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI PADA PT. HALEYORA POWER UNIT MANBIL RAYON CILEGON BANTEN - ., Fatari (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
The purpose of this study is to determine the direct effect of work mutations on employee performance at PT. Haleyora Power unit Manbil Rayon Cilegon Banten. To find out the direct influence of work spirit on employee performance at PT. Haleyora Power unit Manbil Rayon Cilegon Banten. To find out the direct effect of work mutation and work spirit together on employee performance at PT. Haleyora Power unit Manbil Rayon Cilegon Banten. In this study the method used is quantitative with an associative approach. Associative quantitative research is research that seeks to find the relationship between two or more variables. The relationship can be symmetrical, causal and interactive. A symmetrical relationship is a relationship between two or more variables that happen to come together. A causal relationship is a causal relationship. And interactive relationships are relationships between variables that influence each other. Based on the results of research hypothesis testing, the findings of this study are the influence of work mutations and work morale on employee performance. For the regression equation in this study can be expressed in the following equation Y = 1.688 + 0.696 X1 + 0.104X2. Based on the regression equation above, the constant value is 1.688 which means that if there is no work mutation variable and morale or X = 0 then the employees performance is 1.688. The contribution of work mutations and all work together with the determination coefficient or R Square is 0.821 or 82.1%. This shows that the variables studied are work mutations and work morale have a positive impact on employee performance at 82.1%, while the remaining 17.9% is influenced by variables that are not examined. Based on the results of the analysis and discussion, conclusions can be made as follows: Working mutation variables (X1) and work morale (X2) simultaneously or together have an influence on employee performance (Y) at PT. Haleyora Power unit, Manbil Rayon Cilegon Banten, at a significant level of a = 0.05, thus rejecting Ho and accepting Ha. This also proves that work mutations can be said to develop well at PT. Haleyora Power unit Manbil Rayon Cilegon Banten.